“Co-teaching as an assessment resource” : Perceptions of Finnish University Teachers’ Assessment in Higher Education - Hietamäki, Ulla; Lavanti, Lassi; Vesaranta, Helena (Lapin yliopisto, 2024)
In university teaching, assessment culture shapes the roles, power dynamics and interactions that occur during the implementation of competence assessment. The pedagogical expertise of the higher education teacher becomes apparent when conducting assessments. Assessment is at a turning point in higher education, and the university teacher's assessment skills now include an ability to involve students as active participants in the assessment process. The data was collected by autoethnographic lenses from new Finnish university teachers (N=3), and the study was used content analysis informed by constructivist grounded theory (Charmaz, 2014). The study examines university teachers' perceptions and practices of assessment and assessment culture in Finnish universities. This study aims to describe the experiential perceptions of how the assessment culture and its practices are perceived by new university teachers. The results show that co-teaching is seen as an asset that supports teacher development. Secondly, assessment built on a clear criteria- and goal-oriented basis increases transparency and consistency in competency assessment. Thirdly, formative assessment is seen to be crucial in competence assessment contributing to the quality and variety of assessment. At the same time, however, this challenges the teacher on how to make formative assessment visible in summative assessment. Thus, we argue that ongoing, open reflection by both the teacher and the university community is a crucial factor in furthering assessment implementation and creating an assessment culture. nonPeerReviewed